Development of an efficient method for selection of stable cell pools for protein expression and surface display with Expi293F cells. (2nd March 2023) - Chen, Chuan; Wang, Zening; Sun, Zehua; Li, Wei; Dimitrov, Dimiter S.
Abstract: Compare with transient expression, stable cell lines generally have higher productivity and better quality for protein expression. However, selection of stable cell line is time‐consuming and laborious. Here we describe an optimized selection method to achieve high‐efficient stable cell pools with Expi293F suspension cells. This method only takes 2–3 weeks to generate stable cell pools with 2‐ to 10‐fold higher productivity than transient gene expression (TGE). In fed‐batch culture with Yeastolate, >1 g/L yield was achieved with our KTN0239‐IgG stable cell pool in shaker flasks. This method can be also applied to efficiently display proteins on the cell surface. Significance statement: In this manuscript, we optimized the stable cell pool selection methods based on Expi293F suspension cells for protein expression and display. With this method, high‐expression stable cell pools were generated within 2–3 weeks. This system is an efficient platform for stable cell pool generation which avoid time‐consuming and laborious single cell clone selection process and may be useful for laboratory protein production and preclinical development.